Douglass C. North, Institutions, Institutional Change and Econonomic Performance, Cambridge: Cambridge University Press, 1990, 152 s., $ 12,00 (pb.); Margaret Levi, Of Rule and Revenue, Berkeley: University of California Press, 1988, 2535., $ 15,00 (pb.). - Sonne Nørgaard, Asbjørn (Politica, 1992)
-